2015
DOI: 10.1159/000381547
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Thyroid Autoantibodies in Children, Adolescents and Young Adults with Type 1 Diabetes in Kuwait

Abstract: Objective: To investigate the prevalence of thyroid autoimmunity among children and adolescents with type 1 diabetes in Kuwait. Subjects and Methods: Ina mixed cross-sectional and longitudinal study,anti-thyroid peroxidase (anti-TPO) and anti-thyroglobulin (anti-TG) were measured in 232 subjects (118 males and 114 females) with type 1 diabetes. Results: The mean age of the total study population was 10.9 ± 3.6 years (range 1-21), and the median diabetes duration was 3.9 years (range 0-16). At the initial scree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(15 citation statements)
references
References 29 publications
2
12
1
Order By: Relevance
“…Our results are consistent with existing studies that notice thyroid autoimmunity more often in girls (33,39) and increase by 4.6% in prevalence of hypothyroidism (including subclinical cases) for every 10-year increase of age in T1D and with diabetes duration (15). These findings correlate with overall trends of thyroid autoimmunity incidence in other countries (39,40) and also in Poland (41). Contrary to our findings, the meta-analysis based on 14 studies shows that the risk of thyroid dysfunction is much higher in children in comparison to adults (42).…”
Section: Discussionsupporting
confidence: 92%
“…Our results are consistent with existing studies that notice thyroid autoimmunity more often in girls (33,39) and increase by 4.6% in prevalence of hypothyroidism (including subclinical cases) for every 10-year increase of age in T1D and with diabetes duration (15). These findings correlate with overall trends of thyroid autoimmunity incidence in other countries (39,40) and also in Poland (41). Contrary to our findings, the meta-analysis based on 14 studies shows that the risk of thyroid dysfunction is much higher in children in comparison to adults (42).…”
Section: Discussionsupporting
confidence: 92%
“…The close relationship between type 1 diabetes and thyroid autoimmunity has been reported in many previous studies. 12,[15][16][17] In recent years, some studies have shown that the elevated levels of thyroid autoantibodies are correlated with T2DM. 18,19 Osei Sarfo-Kantanka et al found a higher prevalence of thyroid autoimmunity in T2DM patients compared to healthy people.…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of thyroid autoantibodies is similar to the prevalence measured in the Western (Jeddah; 14%) 16 but higher than Central KSA (Riyadh; 8.1%). 17 The prevalence of T1DM reported in Jordan (9.2%), 18 Egypt (12%), 19 and Sudan (7.3%) 20 showed some variations, and a much higher prevalence was reported in studies of thyroid autoantibodies in T1DM children from Kuwait (24.6%), 21 and Libya (31.4%). 22 Global variations in prevalence have been shown in different studies.…”
Section: Discussionmentioning
confidence: 95%